SK609, a novel dopamine D3 receptor agonist and norepinephrine transporter blocker with putative pro-cognitive actions, does not induce psychostimulant-like increases in risky choice during probabilistic discounting - Christopher P. Knapp; Brooke Fallon; Sandhya Kortagere; Barry D. Waterhouse; Stan B. Floresco; Rachel L. Navarra (Psychopharmacology, 2025)
Rationale Psychostimulants, such as amphetamine (AMPH) and methylphenidate (MPH), non-selectively elevate extracellular concentrations of the catecholamine neurotransmitters, dopamine (DA) and norepinephrine (NE), and are common pharmacological strategies used to improve prefrontal cortex (PFC)-dependent cognitive dysfunction. However, this approach can be problematic given AMPH has been shown to increase preference for risky choices in a rodent assay of risk/reward decision making. SK609 is a novel NE reuptake blocker that selectively activates DA D3 receptors without affinity for the DA transporter. SK609 has been shown to improve cognitive performance without increasing psychostimulant-like spontaneous locomotor activity, suggesting SK609 may benefit neurocognitive function without psychostimulant-like side effect liability. Objectives We compared AMPH, MPH, and SK609 within dose ranges that display their cognitive enhancing properties in a probabilistic discounting task (PDT) of risk/reward decision making behavior to assess their potential to increase risky choice preference. Methods Rats chose between small/certain rewards delivered with 100% certainty and large/risky rewards delivered with descending probabilities across a session (100 − 6.25%) following administration of AMPH (0.25-1 mg/kg), MPH (2–8 mg/kg), and SK609 (4 mg/kg). Results AMPH and MPH increased risky choice behavior at doses previously reported to enhance cognition, whereas SK609 did not. AMPH and MPH also reduced sensitivity to non-rewarded risky choices. Conclusions These data highlight the combination of NE transporter blockade and selective D3 activation in pro-cognitive action without psychostimulant-like side effect liability. The absence of DA transporter blockade and non-selective dopaminergic activation are beneficial properties of SK609 that differentiates it from the traditional pro-cognitive psychostimulants.